EFFECTIVE STRATEGIES FOR MANAGING CREDIT RISKS IN COMMERCIAL BANKS - Yormatov Ilmidin Toshmatovich; Umarov Bakhromjon Kabiralievich (Scholars Digest Publishing, 2024)
This article explores effective strategies for managing credit risk in commercial banks. It examines the basic principles and methods of assessing and managing credit risks and also offers recommendations for their application. The authors analyse various approaches to credit risk management, including credit policies, credit scoring procedures, borrower monitoring, and the use of credit risk insurance. Based on best practices in the global banking sector, the article offers recommendations for commercial banks to develop and implement effective credit risk management strategies.
Keywords: credit risks, risk management, commercial banks, effective strategies, credit policy, credit scoring, monitoring of borrowers, credit risk insurance, financial management, banking sector.